Developing application in JavaScript - comparison of commercial and open source solution - Jabłońska, Patrycja (Journal of Computer Sciences Institute, 2018)
Subject of this article is comparative analysis of two popular frameworks in JavaScript: AngularJS (open source) and Ext JS (commercial package). There were two original applications used for this study, each implemented in one of frameworks. Structure of applications, difficulty of implementing GUI components, code metrics, documentation availability and community support were compared. Results were presented in charts.